2011
DOI: 10.1016/j.pscychresns.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Early-life stress, corpus callosum development, hippocampal volumetrics, and anxious behavior in male nonhuman primates

Abstract: Male bonnet monkeys (Macaca radiata) were subjected to the Variable Foraging Demand (VFD) early stress paradigm as infants, MRI scans were completed an average of four years later, and behavioral assessments of anxiety and ex-vivo corpus callosum (CC) measurements were made when animals were fully matured. VFD rearing was associated with smaller CC size, CC measurements were found to correlate with fearful behavior in adulthood, and ex-vivo CC assessments showed high consistency with earlier MRI measures. Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
102
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 51 publications
8
102
0
1
Order By: Relevance
“…During adolescence, striking changes in amygdalahippocampal-mPFC connectivity are observed (Pattwell et al, 2011), and, by adulthood, aversive learning is supported by strong interconnections among the amygdala, hippocampus, and mPFC in nonhuman animals (LeDoux et al, 1990;Corcoran and Quirk, 2007;Sierra-Mercado et al, 2011) and human adults (Fullana et al, 2016;Greco and Liberzon, 2016). Rodent models have revealed that maternal separation leads to precocious prefrontal and hippocampal maturation (Huang et al, 2005;Muhammad et al, 2012), and adult-like aversive learning and anxiety during development (Moriceau and Sullivan, 2006;Ono et al, 2008;Callaghan and Richardson, 2011). Importantly, while maternal deprivation accelerates aversive-learning processes, it may slow or impair cognitive development (Hulshof et al, 2011), suggesting that stress-induced changes are not uniform.…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…During adolescence, striking changes in amygdalahippocampal-mPFC connectivity are observed (Pattwell et al, 2011), and, by adulthood, aversive learning is supported by strong interconnections among the amygdala, hippocampus, and mPFC in nonhuman animals (LeDoux et al, 1990;Corcoran and Quirk, 2007;Sierra-Mercado et al, 2011) and human adults (Fullana et al, 2016;Greco and Liberzon, 2016). Rodent models have revealed that maternal separation leads to precocious prefrontal and hippocampal maturation (Huang et al, 2005;Muhammad et al, 2012), and adult-like aversive learning and anxiety during development (Moriceau and Sullivan, 2006;Ono et al, 2008;Callaghan and Richardson, 2011). Importantly, while maternal deprivation accelerates aversive-learning processes, it may slow or impair cognitive development (Hulshof et al, 2011), suggesting that stress-induced changes are not uniform.…”
Section: Significance Statementmentioning
confidence: 99%
“…Rodent models have revealed that maternal separation leads to precocious prefrontal and hippocampal maturation (Huang et al, 2005;Muhammad et al, 2012), and adult-like aversive learning and anxiety during development (Moriceau and Sullivan, 2006;Ono et al, 2008;Callaghan and Richardson, 2011). Importantly, while maternal deprivation accelerates aversive-learning processes, it may slow or impair cognitive development (Hulshof et al, 2011), suggesting that stress-induced changes are not uniform. This is in line with broader evidence suggesting that cognitive and emotional trajectories are not uniform in typical or atypical development (Reichenberg et al, 2010).…”
Section: Significance Statementmentioning
confidence: 99%
“…Adult-restraint stress leads to reversible decreases in dendritic arborization and volume in prefrontal and hippocampal brain regions (16)(17)(18) but lasting amygdaloid neuronal hypertrophy and anxiety-like behavior (19). In contrast, studies of ELS (20)(21)(22)) (e.g., removal of the dam) show deficits in adult hippocampal-dependent memory but inconsistent effects on anxiety-like behaviors (15,23,24), with the specific type of deficit varying as a function of task and age of testing. For example, Raineki et al showed that ELS leads to social behavioral deficits in preweaned rodents but later depressive-like symptoms in adolescent rodents (25).…”
mentioning
confidence: 99%
“…Generally, it is now accepted that ELS can produce changes, most permanently, at multiple levels [25,27]. Following ELS, for example, the overall volume of the hippocampus [28][29][30], corpus callosum [31][32][33], and cortex [34][35][36] all becomes smaller, compared to that of those brain regions in age-matched subjects. Besides these neuroanatomical changes, the neuronal activity and the synaptic function in the brain in ELS-victims are impaired [37][38][39], and most neurotransmitter systems are significantly affected too.…”
Section: Introductionmentioning
confidence: 99%